Mikrostruktur Semikonduktor GaN di Atas Substrat Silikon Dengan Metode Sol-Gel - Sutanto, Heri; Nurhasanah, Iis; Istadi, Istadi; Maryanto, Maryanto; Ambikawati, Wahyu; Marlini, Nofi (BERKALA FISIKA, 2010)
Gallium nitride (GaN) semiconductor thin films have been successfully deposited on Si substrate (004) by sol-gel method. Gel prepared from the crystal gallium-citrate-amines. These crystals formed from a solution containing the ions Ga+3 and citric acid (CA). Gel in place on the substrate and then rotated with a speed of 1100 rpm. The gel layers are obtained and then placed on the programmable furnace. Deposition temperature varied of 800, 900 and 1000oC in a nitrogen gas environment during 2 hour. The crystal quality of GaN thin films have characterized by XRD measurement. The surface morphology and cross section of the films observed by SEM. The film compositions determined by EDX characterization. The results showed that all the GaN thin films on silicon substrate have oriented polycrystalline structure. The crystal quality of GaN film is formed is influenced by the deposition temperature. In a deposition temperature range is used, increasing the deposition temperature can improve the crystal quality of GaN films. Â  Keywords: GaN Thin Films; Spin-Coating Technique; Silicon Substrate